Histological typing of tumours of the upper respiratory tract and ear - Shanmugaratnam, K; Sobin, Leslie H (Springer, 1991)
Tumours and tumour-like lesions occurring in the Upper Respiratory Tract andEar are classified and defined using internationally accepted terminology and diagnostic criteria. The second edition of this WHO publication is substantially revised and expanded in collaboration with pathologistsin 8 countries.
International histological classification of tumours
Keywords: nádory dýchací soustavy; Neoplasms by Histologic Type; nádory podle histologického typu; nádory ucha; Respiratory Tract Neoplasms; otorinolaryngologické nádory; Ear Neoplasms; Otorhinolaryngologic Neoplasms; patologie; onkologie